Analysis of a coal-fired power system integrated with a reheat S-CO2 cycle. (February 2019) - Sun, Enhui; Xu, Jinliang; Hu, Han; Zhu, Bingguo; Xie, Jian; Zheng, Yawen
Abstract: As a high-performance power cycle, S-CO2 cycle has drawn a lot of attention in various energy utilization field. As one of the clean and efficient forms for coal utilization, coal-fired power plants still need novel power generation systems to have rational use of coal. So, it is necessary to explore the characteristic when a coal-fired power system integrated with S-CO2 cycle. However, this application is confronted with many challenges related to boiler, such as pressure drop problem due to large mass flow rate and residual heat problem due to narrow CO2 temperature difference. Focus on the residual heat problem, in this paper, a coupling analysis model between boiler and reheat S-CO2 cycle is established. The proposed system consists of a thermal-hydraulic calculation module in boiler, a residual heat treatment module in tail flue and a thermodynamic calculation module of S-CO2 cycle. The three modules can make the calculation results more credible for cycle characteristics. All the modules are programmed by Fortran. Base on the analysis result, the residual heat problem can be solved by raising turbine inlet pressure. But when turbine inlet temperature is higher, the turbine inlet pressure will be raised unacceptable. By adding a flue gas cooler (FGC), above limitation will be removed. So, in a certain temperature range, adding an FGC is a simple and effective way to solve residual heat problem.